Long-term outcome of an unusual haemophilic pseudotumour - Serban, M.; Mihailov, D.; Savescu, D.; Bordos, D.; Niculescu, S. Talpos; Jinca, C.; Lacatusu, A.; Siebeck, M.; Schramm, W. (Hämostaseologie, 2012)
Haemophilia, a lifelong congenital bleeding disease, is a highly demanding disorder, due to the costs of its replacement therapy. In the absence of this pivotal treatment, life expectancy and quality of life are deleteriously affected.As illustration, we present a 14 years long follow- up of a patient with severe haemophilia A, treated sporadically with fresh plasma, cryoprecipitate and factor concentrates, who developed a giant iliopsoas pseudotumor. Since he was an infant, under on demand therapy with fresh frozen plasma, cryoprecipitate and low doses of factor concentrates he presented many spontaneous bleedings, developing multiple disabling arthropathies. At the age of 14 years, an iliopsoas hematoma occurred, which relapsed several times, developing an iliopsoas pseudotumour. After 5 years, sepsis with Klebsiella was diagnosed. A CT scan revealed fistula between the pseudotumor and the gut. Under antibiotics, the evolution of sepsis improved, but over a period of 10 months 5 episodes of haematemesis and melena, followed by one episode of macroscopic haematuria occurred; two months later he developed an inguino-crural mass, which fistulized through the abdominal wall. A mixt german-romanian team solved the clinical concern. After 108 hospitalization days and consumption of 104 840 IU factor VIII he left the clinic in good condition. One year later, the temporary colostomy with anus praeter was closed. The follow-up reveals now, after almost 10 years with favourable outcome, that the patient is well, active within his family and profession.
Keywords: Haemophilia; iliopsoaspseudotumour; fistula